Dietary Antioxidants Decrease Serum Soluble Adhesion Molecule (sVCAM-1, sICAM-1) but not Chemokine (JE/MCP-1, KC) Concentrations, and Reduce Atherosclerosis in C57BL but Not ApoE*3 Leiden Mice Fed an Atherogenic Diet. Issue 4 (9th June 2013) - Murphy, Nuala; Grimsditch, David C; Vidgeon-Hart, Martin; Groot, Pieter H.E.; Overend, Philip; Benson, G. Martin; Graham, Annette
Abstract : Dietary antioxidants are reported to suppress cellular expression of chemokines and adhesion molecules that recruit monocytes to the artery wall during atherosclerosis. In the present study we measured the effect of feeding apoE*3 Leiden mice or their non-transgenic (C57BL) littermates with atherogenic diets either deficient in, or supplemented with, dietary antioxidants (vitamin E, vitamin C and β-carotene) for 12 weeks, on serum levels of CC (JE/MCP-1) and CXC (KC) chemokines and soluble adhesion molecules (sVCAM-1, sICAM-1) and atherosclerotic lesion size. ApoE*3 Leiden mice developed gross hypercholesterolaemia, and markedly accelerated (10–20 fold; P < 0.0001) atherogenesis, compared with non-transgenic animals. Antioxidant consumption reduced lesion area in non-transgenic, but not apoE*3 Leiden, mice. Serum sVCAM-1 and sICAM-1 levels were significantly ( P < 0.0001) increased (sVCAM-1 up to 3.9 fold; sICAM-1 up to 2.4 fold) by 4—8 weeks in all groups, and then declined. The initial increase in the concentration of adhesion molecules was reduced by 38%— 61% ( P < 0.05) by antioxidant consumption, particularly in non-transgenic mice. By contrast, serum chemokine levels tended to increase more rapidly from baseline in apoE*3 Leiden mice, compared with non-transgenic animals, but were unaffected by dietary antioxidants. We conclude that dietary antioxidants reduce circulating soluble adhesion molecules and atherosclerosis in C57BL mice.